Union Discourse and Perceived Violation of Contract: A Social Contract-Based Approach - Peyrat-Guillard, Dominique (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2008)
This article proposes a study of the violation of contract process through a case study. The study is based on a discourse of the union, SUD Michelin, which is contrasted both with those of another union, the CFE-CGC Michelin and of the senior management of the corporation. The results highlight the possibility of applying Morrison and Robinson’s (1997) Psychological Contract Violation model at the social contract level. The emotional reactions appearing in the literature, which are associated with contract violations, can be seen in the union discourse of the SUD. The other union does not perceive any breach of contract. These differences may be attributed to the very nature of social contracts—relational in the first case, and more balanced in the second.